2021
DOI: 10.4103/npmj.npmj_495_21
|View full text |Cite
|
Sign up to set email alerts
|

Low Plasma Vitamin D as a Predictor of Uterine Fibroids in a Nigerian Population

Abstract: Background: Uterine fibroid is the most common benign tumour of the uterus and the exact cause is unknown. Vitamin D has been found to inhibit cell proliferation and enhance apoptosis in vitro. Aim: The aim of this study is to compare the plasma level of Vitamin D among women with uterine fibroids and those without uterine fibroids. Materials and Methods: This was an analytical cross-sectional study conducte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 23 publications
0
7
0
Order By: Relevance
“…It is estimated that Vitamin D deficiency affects 25-50% (possibly more) of patients [51]. Several studies found that insubstantial levels of Vitamin D can contribute to the development of UFs in African American, Caucasian, and Asian women alike [52][53][54][55][56][57][58][59][60]. Vitamin D 3 deficiency activates fibroid cell growth, exacerbates DNA damage, and reduces DNA repairability; it promotes uncontrolled proliferation and fibrosis, and increases chronic inflammation.…”
Section: Vitamin Dmentioning
confidence: 99%
See 1 more Smart Citation
“…It is estimated that Vitamin D deficiency affects 25-50% (possibly more) of patients [51]. Several studies found that insubstantial levels of Vitamin D can contribute to the development of UFs in African American, Caucasian, and Asian women alike [52][53][54][55][56][57][58][59][60]. Vitamin D 3 deficiency activates fibroid cell growth, exacerbates DNA damage, and reduces DNA repairability; it promotes uncontrolled proliferation and fibrosis, and increases chronic inflammation.…”
Section: Vitamin Dmentioning
confidence: 99%
“…Vitamin D 3 inhibited TGF-β3-induced protein expression and all TGF-β3-mediated effects involved in the fibrotic processes in leiomyoma. Other studies indicate that increasing Vitamin D levels by one unit can reduce the risk of developing UFs by 4-8% [59,64]. Hajhashemi et al confirmed a significant decrease in leiomyoma size after 10 weeks of vitamin D administration [76].…”
Section: Vitamin Dmentioning
confidence: 99%
“…Although the association between vitamin D and fibroid incidence has not been previously studied, a recent systematic review and additional observational studies report lower concentrations of 25(OH)D among women with prevalent fibroids than those without fibroids (6,(45)(46)(47). The observational studies rely on self-reported fibroid status, and this results in undiagnosed fibroids being included in the ''noncase'' group (5) as well as temporal misclassification of 25(OH)D concentrations.…”
Section: Discussionmentioning
confidence: 99%
“…Studies have reported associations between vitamin D deficiency and impaired fertility, including decreased pregnancy rates and increased risk of pregnancy complications [131,132]. It was reported that the predictors of UFs were fewer hours spent outdoors, middle social class and low vitamin D levels [133]. Vitamin D and its analogs seem to be promising, effective, and low-cost compounds in the management of UFs and their clinical symptoms, and the anti-tumor activities of vitamin D play an important role in UF biology.…”
Section: Vitamin D Serum Level Checkup and Proper Supplementationmentioning
confidence: 99%